The process of eliminating neonatal tetanus in Colombia, 1989-2005 (2014)
Objective To describe the country's progress in eliminating neonatal tetanus based on the information obtained from epidemiologic surveillance Material and Methods A retrospective descriptive study of the epidemiological surveillance of neonatal tetanus in Colombia in the period ranging from 1989 to 2005. Available information was consulted regarding confirmations of this event of interest for Public Health. Results During the study period, a total of 830 cases of neonatal tetanus were reported. In 1989, the rate of neonatal tetanus in Colombia was 0.22 per 1 000 live births. In 2005, this value was reduced to 0.01 cases per 1000 live births; a reduction of nearly 94 %. Conclusions Given the information provided by epidemiological surveillance, Colombia has achieved the goal of maintaining a rate less than 1 case per 1000 live births. Nevertheless, even one case anywhere in the country should be considered a failure of the health care system. © 2016, Universidad Nacional de Colombia. All rights reserved.